2014
DOI: 10.1103/physrevlett.113.254101
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Phase for Stochastic Oscillators

Abstract: Oscillations and noise are ubiquitous in physical and biological systems. When oscillations arise from a deterministic limit cycle, entrainment and synchronization may be analyzed in terms of the asymptotic phase function. In the presence of noise, the asymptotic phase is no longer well defined. We introduce a new definition of asymptotic phase in terms of the slowest decaying modes of the Kolmogorov backward operator. Our stochastic asymptotic phase is well defined for noisy oscillators, even when the oscilla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
108
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(110 citation statements)
references
References 26 publications
2
108
0
Order By: Relevance
“…We also perform numerical simulations of a model of excitable membrane dynamics that was proposed by Izhikevich [25] and is similar to the two-dimensional Morris-Lecar model [26]. Following reference [27] the model is endowed with channel noise, which is due to the finite number of potassium selective channels. The voltage dynamics of the Izhikevich model are given by…”
Section: Izhikevich Model With Ion Channel Noisementioning
confidence: 99%
“…We also perform numerical simulations of a model of excitable membrane dynamics that was proposed by Izhikevich [25] and is similar to the two-dimensional Morris-Lecar model [26]. Following reference [27] the model is endowed with channel noise, which is due to the finite number of potassium selective channels. The voltage dynamics of the Izhikevich model are given by…”
Section: Izhikevich Model With Ion Channel Noisementioning
confidence: 99%
“…1 limit cycle [10] and/or the amplitude variability in the transversal direction of the limit cycle [11][12][13]. Other papers derive related descriptions of the asymptotic phase of stochastic oscillators [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in [4] we showed that the persistent sodium-potassium model driven by channel noise [1,2] can exhibit sustained subthreshold oscillations alternating with large amplitude limit cycle oscillations (action potentials). Under these conditions the eigenvalue spectrum of the adjoint equation [2] has two complex eigenvalue pairs with similar real parts. The system violates our criterion iii, and we do not expect it to have a single well defined phase.…”
mentioning
confidence: 99%
“…In [2] we considered, for instance, a heteroclinic 2d system that does not possess a limit cycle in the deterministic limit. Pikovsky's first example, a spiral focus with additive noisė…”
mentioning
confidence: 99%
See 1 more Smart Citation